Technological trends, emerging applications and metallurgical strategies in antimony recovery from stibnite. (1st January 2022) - Dembele, Seydou; Akcil, Ata; Panda, Sandeep
Highlights: Antimony usage is gaining importance in several emerging technologies. Current technological and market trends of antimony are presented. Extractive metallurgy for Stibnite ore processing is comprehensively discussed. Antimony purification and recovery processes and their challenges are reviewed. Future research and industrial needs are highlighted. Abstract: Developed economies such as the USA and European Union (EU) have classified antimony as a critical raw material. China leads the global antimony production (67% on an average from 2015 to 2019) followed by Russia and Tajikistan. Antimony has been applied in the industry (plastics, etc.) and new/emerging technologies (cell panels, infrared, etc.) where antimony trioxide (Sb2 O3 ) is its most produced and used compound. With technological advances, recent trends indicate a growing demand for this metal; however, with the on-going production rate, antimony is anticipated to become one of the scarcest metals by 2050. Several minerals of antimony exist; nevertheless, stibnite (Sb2 S3 ) is the primary mineral. Extractive metallurgical routes such as pyro and hydro-metallurgy have found industrial applications for stibnite processing; however, bio-hydrometallurgy is slowly gaining momentum. In this piece of review, the world-wide scenario of antimony production, recent market trends along with the common and current research advances related to applications of antimony in emerging technologies is presented. Comprehensive details along with the recent advances related to stibnite processing through the aforementioned extractive metallurgy routes, their technological improvements and antimony purification/recovery methods from leach solutions are also discussed. Furthermore, the future perspectives in terms of research and industrial needs are discussed and summarized.